Protestens evindelige genkomst? Feministisk plakatkunst, genfortolket - Fabricius, Charlotte J. (Passage - Tidsskrift for litteratur og kritik, 2025)
“The Eternal Return of the Protest? Feminist Poster Art, Reimagined” The article discusses the place of historical feminist posters, especially from the 1970s, in contemporaryfeminism. By analysing the temporalities, af- fects, and materiality of a recent book of feminist poster art, Ican’t believe I still have to protest this shit (edited by Jessica Hallbäck, Gutkind 2023), the article argues for thesuitability of a transhistorical approach when making use of past pro- test art in the age of digital-first feminism.